Grammar-Related Autonomous Supportive Practice (GRASP) version 2: a language learning game for improvement of english grammar comprehension and memory retention / Noraziah Mohd Amin ...[et al.] - Mohd Amin, Noraziah; Abdul Rahman, Noor Azam Abdul Rahman; Razali, Wan Noorli; Abu Bakar, Mohd Saifulnizam; Sharipudin, Mohamad-Noor; Mohd Amin, Norhasni; Abdul Wahab, Mohd Faisal (Universiti Teknologi MARA, 2018)
It is of fundamental importance to use effective techniques for learning a language since language learning is not easy work and efforts made for this purpose must be retained over time (Wright, Betteridge and Buckby, 2006). Upon realizing this issue with language learning, an English learning tool, Grammar-Related Autonomous Supportive Practice (GRASP) was invented. GRASP is a board game whose central objective is to strengthen grammar comprehension, involving several language components such as "nouns", "pronouns", "adjectives", "adverbs", "verbs", "tenses", "prepositions", and "conjunctions". As GRASP is an acronym created to represent the meaning of the English word, "grasp", the game is intended to improve learners' understanding and memory of English grammar via playing it. The game also involves various aspects that make it more interesting, namely the visual stimuli like the graphics on grammar question cards and a colorful board; the determination of the winner based on who is able to answer the most grammar questions correctly as well as who is the fastest to arrive at the finish line; the penalty for a wrong answer; mystery rewards; and many other fun elements. With all that GRASP can offer, it can be confidently claimed that its novelty value can benefit learners in many ways especially in serving as a fun learning tool for enhancement of grammar understanding, and retention of grammar memory without any need for complicated technical or electronic dependence. Being made of affordable light materials like papers and plastic, GRASP is easily produced and marketable for the reach of many potential users.